Faktor-Faktor yang Memicu Konflik dan Dampak Sosial yang Ditimbulkan untuk Mengurangi Potensi Kekerasan di Lingkungan Sekolah - Arief, Aisah Putri; Ismail, Fadhil Fadhlurahman Putra; Fianden, Fachmi Maya Syafirah; Hosnah, Asmak Ul (Interdisciplinary Explorations in Research Journal, 2025)
The slashing case that occurred in the Pomad area, Bogor, involved two groups of students involved in a conflict that led to violence. This incident attracted public attention and became the focus of the media, considering the increasing number of violence among students. This study aims to analyze the factors that trigger the conflict, the social impacts caused, and preventive measures that can be applied to reduce the potential for violence in the school environment. Data were obtained through interviews with witnesses, analysis of media reports, and discussions with the school. The results of the study indicate that lack of communication and understanding between students, as well as the influence of the social environment, contributed to the incident. Recommendations for conflict prevention in schools include character education programs and increasing the role of parents and the community.